Correlative Atomic Force Microscopy and Localization‐Based Super‐Resolution Microscopy: Revealing Labelling and Image Reconstruction Artefacts. Issue 4 (22nd November 2013) - Monserrate, Aitor; Casado, Santiago; Flors, Cristina
<x xml:space="preserve">Abstract</x> Hybrid microscopy: A correlative microscopy tool that combines in situ super‐resolution fluorescence microscopy based on single‐molecule localization and atomic force microscopy is presented. Direct comparison with high‐ resolution topography allows the authors to improve fluorescence labeling and image analysis in super‐resolution imaging.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>